Survey On Public Perceptions and Satisfactions Toward Public Transportation Services in Negeri Sembilan During COVID-19 - Lee, Xue Jing; Mohd Asrah, Norhaidah (Enhanced Knowledge in Sciences and Technology, 2022)
Public transportation acts as essential transportation to the public, and there are many types of public transportation in Malaysia. However, Negeri Sembilan only consists of bus, taxi, train, and e-hailing services. The service quality issues were the causes of people not being interested in using public transport. Hence, the purpose of this study is to determine the public perception toward public transportation services in Negeri Sembilan by using descriptive analysis, to identify the factors that affect the satisfaction level by using factor analysis, to investigate the public experiences and the solutions by using sentiment analysis and lastly to compare the changes before and during COVID-19 by using importance-performance analysis. The result showed that the people were satisfied with the public transport services in Negeri Sembilan. There were three components of factors that affect the satisfaction level, namely vehicles services, convenience, and additional services and speed. The positive comments were more than the negative comments and the suggestion provided is to offer more promotion and discounts. Lastly, the services such as cleanliness, waiting time, comfortable, cost, safety during journey, easy for booking and punctuality were the services that are performed well and need to be improved in the future.